Womens Participation in Improving the Family Economy, Viewed From an Islamic Perspective - M. Arif Musthofa (Jurnal Al Mujaddid Humaniora, 2020)
Islam wants a view of equality between men and women but they cannot evade from the context of culture at that time which gives more status to men, Women have the right and opportunity to pursue a career by not neglecting their function and position as a woman, a woman may work if there is one of a number of conditions that allow women to work outside the home so it is said that career women must meet certain conditions, gives women the opportunity to work outside the home if the community needs their expertise.